Near-infrared semiconductor photonic switches for quantum sensors - Saleeb-Mousa, Bruce (2022)
The promising performance of atom interferometry in determining precise values of fundamental constants, lends itself to applications in many areas of modern physics and engineering. In particular, the cold-atom gravimeter has proven itself to be a useful tool in determining the local acceleration due to gravity with a precision of delta g/g = 10^-9, with long term stability and accuracy. In recent years, there has been a major incentive to develop these mainly laboratory-based experimental systems towards more compact, portable and eventually commercialised systems. Part of this development involves the design, fabrication and testing of bespoke underpinning technologies such as high performance, low power integrated active optical components which would help to reduce the size, weight and power of these sensors.